Modeling Energy Consumption, Carbon Emission and Economic Growth: Empirical Analysis for Pakistan - Ali, Amjad; Khatoon, Sabila; Ather, Muhammad; Akhtar, Naila (International Journal of Energy Economics and Policy, 2015)
This study examines the short run and long relationship among carbon emission, energy consumption and economic growth in case of Pakistan for the time period 1980 to 2012. For this purpose we have employed Johansen co-integration approach and the results reveal that there exists long run relationship among Energy, Growth and Environment (E-E-E) in Pakistan. It is found that the Environmental Kuznets Curve hypothesis is valid in long run but not in short run. Also there exists unidirectional causality between energy consumption to energy emission in Pakistan. Unidirectional causality also found between financial development and economic growth running from financial development to economic growth. Keywords: Environmental Kuznets Curve, Energy, Growth, Co-integration, Pakistan JEL Classifications: G00; Q43; Q50